Association between serum alanine aminotransferase level and obesity indices in Korean adolescents - Moon Bae Ahn; Woo Ri Bae; Kyung Do Han; Won Kyoung Cho; Kyoung Soon Cho; So Hyun Park; Min Ho Jung; Byung Kyu Suh (Korean Pediatric Society, 2015)
PurposeTo analyze the correlation between serum alanine aminotransferase (ALT) and obesity indices including body mass index (BMI), body fat percentage (BFP), total fat mass (FM), truncal fat mass (TFM), waist circumference (WC), and waist-to-height ratio (WHtR) in Korean adolescents.MethodsThis was a cross-sectional study based on data derived from the 2010-2011 Korean National Health and Nutrition Examination Surveys (KNHANES). Subjects were Korean adolescents aged 10-18 years (871 total; 475 boys and 396 girls) who participated in KNHANES.ResultsIn both sexes, BMI, FM, TFM, WC, and WHtR were higher when ALT levels were in the 4th quartile. In boys, there was a significant positive correlation between ALT level and BMI, BFP, FM, TFM, WC, and WHtR (r=0.55, P<0.0001 for BMI; r=0.52, P<0.0001 for BFP; r=0.58, P<0.0001 for FM; r=0.61, P<0.0001 for TFM; and r=0.56, P<0.0001 for WC; r=0.62, P<0.0001 for WHtR), and the correlation coefficient was higher than that in girls.ConclusionOur results suggest a significant positive association between serum ALT level and obesity indices in male adolescents.